Jejak Sosial Ekonomi dalam Pembentukan Karakter Tanggung Jawab Siswa: Kajian di SDN 07/XI Koto Baru - Yuslimar, Yuslimar; Candra, Hadi; Putra, Pristian Hadi (Ishlah: Jurnal Ilmu Ushuluddin, Adab dan Dakwah, 2024)
A common problem that occurs in schools today is the low level of responsibility among students in their studies. This can be seen from students not taking notes during lessons, only doing assignments when told to, being unable to solve problems, and cheating on assignments by copying or asking others to do their work for them. This occurs due to internal factors within the students themselves, while external factors come from outside, one of which is social and economic factors. The purpose of this study is to investigate the influence of socio-economic factors on students' sense of responsibility at SDN 047/XI Koto Baru. The research design is a mixed-method approach combining qualitative and quantitative methods, using a descriptive analysis with simple regression. The population consists of 152 individuals, with a sample of 60 students from SDN 047/XI Koto Baru. Data collection techniques used questionnaires, while instrument testing employed validity and reliability tests. Qualitative data analysis techniques included data reduction, data display, and drawing conclusions, whereas quantitative data analysis involved normality tests, hypothesis testing, simultaneous tests (F-test), and determination tests (R2). The results of the study on student responsibility at SDN 047/XI Koto Baru indicate that, in general, student responsibility is good and aligns with the indicators of responsibility, including: preparing activity reports both verbally and in writing, performing tasks without being told, demonstrating initiative to address issues within their immediate surroundings, and avoiding dishonesty in task execution.